Complete Sequence of a F33:A-:B- Conjugative Plasmid Carrying the oqxAB, fosA3, and blaCTX-M-55 Elements from a Foodborne Escherichia coli Strain - Wong, Marcus H.; Xie, Miaomiao; Xie, Liqi; Lin, Dachuan; Li, Ruichao; Zhou, Yuanjie; Chan, Edward W.; Chen, Sheng (Frontiers in Microbiology, 2016)
This study reports the complete sequence of pE80, a conjugative IncFII plasmid recovered from an E. coli strain isolated from chicken meat. This plasmid harbors multiple resistance determinants including oqxAB, fosA3, blaCTX-M-55 and blaTEM-1, and is a close variant of the recently reported p42-2 element, which was recovered from E. coli of veterinary source. Recovery of pE80 constitutes evidence that evolution or genetic re-arrangement of IncFII type plasmids residing in animal-borne organisms is an active event, which involves acquisition and integration of foreign resistance elements into the plasmid backbone. Dissemination of these plasmids may further compromise the effectiveness of current antimicrobial strategies.